Asymptotic behavior of spectral of Neumann‐Poincaré operator in Helmholtz system. (28th November 2018) - Fang, Xiaoping; Deng, Youjun; Chen, Xiaohong
Abstract : In this paper, we are concerned with the asymptotic behavior of the Neumann‐Poincaré operator in Helmholtz system. By analyzing the asymptotic behavior of spherical Bessel function near the origin and/or approach higher order, we prove the asymptotic behavior of spectral of Neumann‐Poincaré operator when frequency is small enough and/or the order is large enough. The results show that spectral of Neumann‐Poincaré operator is continuous at the origin and converges to 0 from the complex plane in general.